Incapacity benefits and employment policy - Jonathan Michael Orszag; Dennis J. Snower (Institute for the Study of Labor (IZA), 2002)
The paper explores the employment implications of allowing people the opportunity of using a portion of their incapacity benefits to provide employment vouchers for employers that hire them. The analysis indicates that introducing this policy could increase employment, raise the incomes of incapacity benefit recipients, and reduce employers? labor costs. The analysis explicitly derives the optimal voucher, i.e. the voucher that maximizes employment at no extra budgetary cost. This voucher is shown to depend on the size of incapacity benefits, the separation rate in the absence of the voucher, and the degree of displacement; but it does not depend on the hiring rate. Numerical calculations show the optimal voucher to be large by the standards of many existing employment subsidies.
Keywords: J31; J23; J24; J32; J64; 330; employment policy; labor force participation; incapacity benefits; Arbeitslosenversicherung; Beschäftigungspolitik; Arbeitsangebot; Lohnsubvention; Voucher; Theorie